Prevalence and characteristics of juvenile fibromyalgia syndrome in pediatric rheumatic diseases: A comparative study - Gülcan Özomay Baykal,; Duygu Kurtuluş,; Serap Ata,; Betül Sözeri, (Archives of Rheumatology, 2024)
Objectives: The study aimed to evaluate the frequency of juvenile fibromyalgia syndrome (JFMS) in patients diagnosed with juvenile idiopathic arthritis (JIA) and familial Mediterranean fever (FMF) with joint symptoms and compare them with a healthy control group. Patients and methods: This retrospective study was conducted with 181 participants between January and April 2023. One hundred twenty-one patients with JIA or FMF diagnoses (71 females, 50 males; mean age: 15.6±2.1 years; range, 12 to 23 years) and 60 healthy individuals (36 females, 24 males; mean age: 14.5±1.6 years; range, 12 to 17 years) were included in the patient group and the control group, respectively. The pain and symptom assessment scale was applied for the JFMS diagnosis, and the output data were analyzed with the widespread pain index and symptom severity scale. Results: Of the patient group, 57% (n=69) were diagnosed with FMF, and 43% (n=52) were diagnosed with JIA. When the two groups were compared with those diagnosed with JFMS, statistical significance was detected (p<0.05). Thirteen (87%) of those diagnosed with JFMS were female, and two (13%) were male, with a statistically significant difference. Conclusion: In patients with JIA and FMF who complain of chronic musculoskeletal pain, tiredness, and weakness, JFMS diagnosis should always be considered in the clinical evaluation.